Evaluation of the reproducibility of two techniques used to determine and record centric relation in angle's class I patients - Fernanda Paixão; Wilkens Aurélio Buarque e Silva; Frederico Andrade e Silva; Guilherme da Gama Ramos; Mônica Vieira de Jesus Cruz (University of São Paulo, 2007)
The centric relation is a mandibular position that determines a balance relation among the temporomandibular joints, the chew muscles and the occlusion. This position makes possible to the dentist to plan and to execute oral rehabilitation respecting the physiological principles of the stomatognathic system. The aim of this study was to investigate the reproducibility of centric relation records obtained using two techniques: Dawson's Bilateral Manipulation and Gysi's Gothic Arch Tracing. Twenty volunteers (14 females and 6 males) with no dental loss, presenting occlusal contacts according to those described in Angle's I classification and without signs and symptoms of temporomandibular disorders were selected. All volunteers were submitted five times with a 1-week interval, always in the same schedule, to the Dawson's Bilateral Manipulation and to the Gysi's Gothic Arch Tracing with aid of an intraoral apparatus. The average standard error of each technique was calculated (Bilateral Manipulation 0.94 and Gothic Arch Tracing 0.27). Shapiro-Wilk test was applied and the results allowed application of Student's t-test (sampling error of 5%). The techniques showed different degrees of variability. The Gysi's Gothic Arch Tracing was found to be more accurate than the Bilateral Manipulation in reproducing the centric relation records.